Statistical optimization of zinc oxide nanorod synthesis for photocatalytic degradation of methylene blue - Aini Ayunni Mohd Raub,; Jumril Yunas,; Mohd Ambri Mohamed,; Jamal Kazmi,; Jaenudin Ridwan,; Azrul Azlan Hamzah, (Penerbit Universiti Kebangsaan Malaysia, 2022)
In this work, synthesis process parameters of Zinc Oxide nanorods (ZnO NRs) photocatalyst is optimized using Taguchi Method to obtain the highest degradation rate of Methylene Blue dye, MB. The Taguchi L27 (38) orthogonal array technique was used to determine the optimum conditions for the synthesis of the nanostructured photocatalyst. Eight important synthesis process parameters were chosen in the analysis while the effects of the parameters were studied using signal-to-noise (S/N) ratio analysis using minitab-16. The ZnO NRs photocatalyst was synthesized via solution process route based on the parameters obtained from the layout of the orthogonal arrays. The optimized synthesized nanorods was then characterized using field emission scanning electron microscope (FESEM), X-ray diffraction (XRD), photoluminescence (PL), ultraviolet-visible near-infrared (UV-VIS-NIR), and Raman spectroscopies while the photodegradation of MB was determined by UV-VIS spectrum analysis under ultraviolet light irradiation. The results show that ZnO NRs with hexagonal wurtzite structure and bandgap energy of 3.25 eV have been obtained. The Taguchi analysis based on simulated experimental runs predicted the highest MB degradation percentage of 17.12% that can be achieved under optimum process conditions. Meanwhile, experimental photocatalytic degradation of MB using ZnO NRs synthesized under the same optimum condition achieved a degradation percentage of 17.27%, which deviates only 0.88% from the predicted value. This analysis could give an approach to optimize the synthesis process to ensure the good performance of nano-photocatalyst for the photodegradation of organic contaminations in industrial wastewater in a short time and cost-effective process.